Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik Pada Pembelajaran IPA Materi Pokok Cahaya dan Alat Optik Kelas VIIIA SMP Negeri 1 Wawoni Utara - Asdianti, Asdianti; Tahang, La; Sukariasih, Luh (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to: 1) To describe the science process skills improvement classes learners VIIIA of SMP Negeri 1 North Wawonii taught through guided inquiry learning model; 2) Describe the activities of teachers in science teaching VIIIA grade SMP Negeri 1 North Wawonii on poko material light and an optical instrument with use taught guided inquiry learning model.This type of research is the Classroom Action Research (CAR), which has been conducted in two cycles. Subjects in this study were all learners VIIIA grade SMP Negeri 1 North Wawonii 2018/2019 school year totaling 19 people. The data collected in this study is the science process skills gained from the observation sheet. Data analysis was performed descriptive statistics. From the results of data analysis obtained by valueAverage science process skills of students in the first cycle of 2.3 included in the category enough and for the average value of the activities of teachers in the first cycle is the second cycle 2,9.Padaearned valueAverage science process skills of students in the first cycle of 3.6 included in both categories, and for the average value of teacher activity in the second cycle is 3.61.Based on the results of research and discussion concluded that the science learning in the subject matter of the Light and Optics are taught using guided inquiry learning model has increased in the science process skills and activities of teachers.